Pengaruh Kualitas Layanan Aplikasi Jogja Smart Service terhadap Kepuasan Pengguna - Rahmat Hakim Al Munawar, Alief; Hidayat, Rahmat Rian; Nopriadi, Nopriadi (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2025)
Public information services are a strategic effort to prepare and provide relevant data or messages to users that the quality of available services can meet expectations and good standards. However, there are gaps in some service menus, which should be directly accessible through the application but are redirected to the website. Other shortcomings are evident in the two different operating systems, Android and iOS, which cause poor reviews and affect user satisfaction. The purpose of this study is to determine the influence of the quality of the Jogja Smart Service application on user satisfaction. This study uses a quantitative approach with a survey of 385 respondents determined using the Cochran formula. The app service quality variable is measured based on the Servqual indicators according to Parasuraman (in Kusumah, 2024), namely tangibles, reliability, responsiveness, assurance, and empathy. To measure user satisfaction, five indicators from Doll & Torkzadeh (in Lippert, 2020) are used, namely content, accuracy, format, ease of use, and timeliness. The data were analyzed using simple linear regression with the assistance of IBM SPSS Statistics 27 software. The results of the study indicate that service quality has a positive and significant effect on user satisfaction with a coefficient of determination (R2) of 0.583 or 58.3%, while the remainder is influenced by other variables not examined in this study